2021
DOI: 10.2147/ijn.s290037
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Evaluation of Multiple Biological Activities of Silver Nanoparticles Fabricated from Dragon Tongue Bean Outer Peel Extract

Abstract: Background: The dragon tongue beans are a legume belonging to the Fabaceae family, are rich in protein, starch, fiber, and other micronutrients that have numerous health-promoting benefits. Its peel commonly the waste parts also contains lots of bioactive compounds. Materials and Methods: In the current research, dragon tongue bean peels (DtbP) extract is tested for the existence of phytochemicals. Ag nanoparticles are biosynthesized using DtbP extract. The generated DtbP silver nanoparticle characterization w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The IC 50 values of B, A, E, and OPD are as follows 38.56, 42.19, 44.84, and 47.23 μg/mL, respectively. On the other hand, the Ag nanoparticles synthesized from dragon tongue bean peels (DtbP-AgNPs) possessed an IC 50 value of 88.37 μg/mL as compared to gold nano-bioconjugate B with 38.56 μg/mL, which indicated that B can act as an efficient antioxidant agent. Ascorbic acid served as a standard and exhibited 83.61% inhibition, which is comparable with gold nano-bioconjugate B with 81.25% inhibition.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The IC 50 values of B, A, E, and OPD are as follows 38.56, 42.19, 44.84, and 47.23 μg/mL, respectively. On the other hand, the Ag nanoparticles synthesized from dragon tongue bean peels (DtbP-AgNPs) possessed an IC 50 value of 88.37 μg/mL as compared to gold nano-bioconjugate B with 38.56 μg/mL, which indicated that B can act as an efficient antioxidant agent. Ascorbic acid served as a standard and exhibited 83.61% inhibition, which is comparable with gold nano-bioconjugate B with 81.25% inhibition.…”
Section: Results and Discussionmentioning
confidence: 99%
“…These analytical methods such as UV-VIS spectral study, energy-dispersive X-ray spectroscopy analysis, Fourier transform infrared spectroscopy analysis, scanning electron microscopy study, X-ray powder diffraction study, Dynamic light scattering, and zeta potential were used to characterize the BdkR-AgNPs according to standard techniques. 5 , 34 , 35 The preliminary synthesis of the BdkR-AgNPs was confirmed by scanning between 300 and 700 nm using the UV-VIS spectrophotometer (Multiskan Go; Thermo Scientific, Waltham, MA, USA). The morphology of the synthesized BdkR-AgNPs was characterized by the SEM machine (Hitachi S-3000N, Tokyo, Japan) and the elemental composition was determined by an EDX machine attached to the SEM.…”
Section: Methodsmentioning
confidence: 99%